3D Electron Diffraction on Nanoparticles: Minimal Size and Associated Dynamical Effects - Cordero Oyonarte, Erica; Rebecchi, Luca; Gholam, Saleh; Faye Diouf, Moussa D; Bigard, Edma; Pralong, Valérie; Prestipino, Carmelo; Kriegel, Ilka; Castellanos-Aliaga, Ana; Hadermann, Joke; Gemmi, Mauro; Palatinus, Lukas; et al. (ACS nano, 2025)
Over the past decade, advances in electron diffraction (ED) have significantly improved the determination and refinement of crystal structures, making it a viable alternative to traditional X-ray diffraction (XRD), especially for very small volumes, such as nanoparticles (NPs). This work evaluates the application of advanced 3D ED techniques to the analysis of isolated NPs, focusing on their efficacy and limitations in terms of crystal size and accuracy of results. Our investigation begins by addressing the challenges of obtaining 3D ED data for NPs, including sample preparation, instrument capabilities, and the choice of 3D ED methods. We find that 3D ED can provide highly accurate structure refinements for crystals in the 50-100 nm range and is also effective for the analysis of NPs as small as 10 nm. While kinematical approximations often provide accurate refinements similar to those obtained from powder XRD, the accuracy depends on the specific data set and may not always align with traditional reliability indicators. Our study shows that dynamical scattering effects, even in tiny crystals, challenge the assumption that they are negligible in thin crystal scenarios. Addressing these effects through full dynamical refinement significantly improves the accuracy and reliability of the structure determination. This report suggests a paradigm shift in viewing dynamic scattering effects not as mere obstacles but as opportunities to explore crystal structures in greater detail on smaller scales. By embracing these complexities, 3D ED can provide precise and reliable structural insights that are critical to the advancement of nanotechnology and materials science.
Keywords: crystallography; electron microscopy; electron diffraction; oxide nanoparticles; dynamical refinement